‘At this [adherence] club, we are a family now’: A realist theory-testing case study of the antiretroviral treatment adherence club, South Africa - Ferdinand C. Mukumbang; Brian van Wyk; Sara Van Belle; Bruno Marchal (Southern African Journal of HIV Medicine, 2019)
Background: An estimated 7.9 million people were living with HIV in South Africa in 2017, with 63.3% of them remaining in antiretroviral therapy (ART) care and 62.9% accessing ART. Poor retention in care and suboptimal adherence to ART undermine the successful efforts of initiating people living with HIV on ART. To address these challenges, the antiretroviral adherence club intervention was designed to streamline ART services to ‘stable’ patients. Nevertheless, it is poorly understood exactly how and why and under what health system conditions the adherence club intervention works.